The Effect of Physical Activity on Physical Health: A Literature Study - Eric, Eric (Journal of Salutare, 2025)
The decline in physical activity in modern society has become one of the main causes of the increasing prevalence of non-communicable diseases such as obesity, hypertension, and diabetes. Physical activity has a major contribution to improving physical health, including cardiorespiratory endurance, muscle strength, flexibility, balance, and body composition. This study aims to examine in depth the effect of physical activity on physical health through qualitative methods based on literature studies. Data were collected from various scientific journals, WHO reports, and relevant reference books in the period 2015–2025. The results of the study indicate that routine physical activity, whether in the form of aerobic exercise, strength training, or flexibility training, has a significant impact on improving physical fitness and mental health. In addition, it was also found that public awareness of the importance of physical activity is still low, so community-based education and interventions are needed. This study emphasizes the importance of integrating physical activity into daily life as a preventive measure that can support quality of life. This study is expected to be a reference in formulating health policies and strategies for promoting an active lifestyle based on scientific evidence.